Design selection of floating brake calliper magnesium hybrid composites - Chiam, Siew Ting (2016)
This thesis deals with material selection and design selection of high performance floating brake calliper. The main function of brake system is to decelerate or stop a car. Disc brake system consist of brake rotor, brake pads and brake calliper. Most of the commercial vehicles use brake calliper made of Gray cast iron which possess heavy weight results in high fuel consumption. Another major problem is calliper being deflection during clamping action, known as “bending of bridge” will results in extended pedal travel since additional braking fluid volume is required to compensate for deflections, reduce comfort, driving feelings and safety of vehicle. The demand of Metal Matrix Composites (MMC) is greatly increased in automotive industry since it having a lower density, higher strength and comparable modulus of elasticity as compared to Gray cast iron. The objective of this thesis is to study the advantages of Magnesium hybrid MMC to replace conventional brake calliper and proposed few innovative design alternatives for automotive industry. This is done by creating an original brake calliper and validate for appropriate material using Finite Element Analysis (FEA), followed by select optimum design. In design selection, Quality Function Deployment (QFD) approach was used to rank the design parameters, few alternative designs were created using CatiaV5R17 and analyzed for static structural analysis using FEA. In the end, best floating brake calliper design among those alternative designs was selected using Super Decision software. For further research, these fresh designs could be act as benchmark for further developed and tested for automotive applications.